2009
DOI: 10.1128/aac.01024-08
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Unbalance in Pseudomonas aeruginosa Isolates from Cystic Fibrosis Patients

Abstract: Retrospective analysis of 189 nonredundant strains of Pseudomonas aeruginosa sequentially recovered from the sputum samples of 46 cystic fibrosis (CF) patients over a 10-year period (1998 to 2007) revealed that 53 out of 189 (28%) samples were hypersusceptible to the ␤-lactam antibiotic ticarcillin (MIC < 4 g/ml) (phenotype dubbed Tic hs ). As evidenced by trans-complementation and gene inactivation experiments, the mutational upregulation of the efflux system MexXY was responsible for various degrees of resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 87 publications
5
67
2
Order By: Relevance
“…The range of overexpression of mexY varied from 6.76-to 73-fold. It has been suggested that MexXY expression contributes not only to the antibiotic resistance of CF P. aeruginosa isolates but also to its adaptive strategy in the CF lung environment (Smith et al 2006;Vettoretti et al 2009). Widespread expression of MexXY pump in the CF isolates we tested does suggest that this pump may have a role to play that goes beyond their antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The range of overexpression of mexY varied from 6.76-to 73-fold. It has been suggested that MexXY expression contributes not only to the antibiotic resistance of CF P. aeruginosa isolates but also to its adaptive strategy in the CF lung environment (Smith et al 2006;Vettoretti et al 2009). Widespread expression of MexXY pump in the CF isolates we tested does suggest that this pump may have a role to play that goes beyond their antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, these mutations cause amino acid changes that make a pump more efficient at extruding the antibiotics out of the cell. For instance, Vettoretti et al (252) described an F1018L substitution in MexY, an RND transporter of P. aeruginosa, which increased resistance to aminoglycosides, fluoroquinolones, and the ␤-lactam cefepime, mediated by the MexXY efflux pump. Notably, this mutation was present in clinical isolates from cystic fibrosis (CF) patients.…”
Section: Mutational Resistance Related To Efflux Pumpsmentioning
confidence: 99%
“…Upregulation of mexXY by antimicrobials or fmt/ folD mutations is dependent upon a gene, PA5471, encoding a conserved hypothetical protein whose expression is also promoted by ribosome-disrupting antimicrobials (34) and by fmt/ folD mutations (6). Despite this primary link to translation disruption, the MexXY-OprM efflux system is a significant determinant of resistance to antimicrobials in clinical isolates, particularly aminoglycosides (19,40,52) but also ␤-lactams (3,19,23,37,51). Indeed, while it is uncommon as a mechanism of aminoglycoside resistance in most clinical strains of P. aeruginosa, MexXY-OprM is the predominant mechanism of resistance to these agents in cystic fibrosis (CF) isolates (19,40,52).…”
mentioning
confidence: 99%